Multidimensional Sustainability Drivers and Asset Efficiency: Moderating Role of Environmental Performance - Wulandari, Linda Ayu; Aini, Inka Nur; Ratnawati, Dewi (Jurnal ASET (Akuntansi Riset), 2026)
This study aims to examine the effect of multidimensional sustainability practices, including circular economy practices, environmental investment, and corporate sustainability disclosure, on asset efficiency, with environmental performance as a moderating variable. The research employs a quantitative approach using panel data from energy sector companies listed on IDX period 2020–2024, with samples selected through purposive sampling based on firms that consistently publish annual and sustainability reports, resulting in 37 companies and 185 observations analyse by Moderated Regression Analysis with E-Views 13. The results show that circular economy practices have a positive and significant effect on asset efficiency, indicating that resource optimization and waste reduction enhance asset utilization. In contrast, environmental investment has a negative effect in the short term, suggesting that high environmental costs and delayed benefits reduce efficiency. Corporate sustainability disclosure does not significantly affect asset efficiency, indicating that disclosure tends to be symbolic rather than operational. Environmental performance has a positive direct effect on asset efficiency and acts as a quasi-moderator. However, it weakens the relationship between circular economy practices and sustainability disclosure on asset efficiency, while it does not moderate the effect of environmental investment. These findings imply that sustainability practices do not automatically improve efficiency, as their effectiveness depends on implementation quality and cost structure. This study contributes by integrating multiple sustainability dimensions within an efficiency-based framework and highlighting the dual role of environmental performance as both a performance driver and a contextual constraint.